Pengembangan Sistem Informasi Perpustakaan Berbasis Website Pada SMK Negeri 4 Pontianak - Dellaviani Oktavianti; Erni Fatmawati; Ryan Permana (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
This research aims to determine the development, feasibility, and how users respond after implementing a website-based library information system at SMK Negeri 4 Pontianak. This research uses research and development methods or in English Research and Development (R&D) with the Richey and Klein model. The subjects in this research are: development consisting of 2 system experts, namely 1 lecturer and 1 IT staff at SMK Negeri 4 Pontianak to measure the feasibility of the program in terms of appearance, design and function of the program while the product trial subjects in this research were 2 students from each department at SMK Negeri 4 Pontianak and 2 librarians with a total of 30 test subjects. The procedures in this research are planning, production, evaluation. The tools used to collect data in this research are interviews, documentation and questionnaires. To analyze the data, researchers applied quality analysis regarding aspects of ease of use and navigation, aesthetics or beauty and technical quality. Based on the results of the analysis, researchers found that the library application developed using the Richkey and Klein model had been created optimally by prioritizing functions and information to help users use the application, and also provided an attractive appearance so that users could easily use the application. In the development used by the Richkey model, Klein has 3 stages used, namely Planning, in this stage the researcher determines the product to be developed along with searching for information related to the product that will be made. After that, the second stage is production, namely the manufacturing design that will be used to create the application and that third is evaluation, namely assessing the applications that have been created and correcting deficiencies in the assessment of the applications created. The library application developed is very suitable for use based on data that has been obtained through system expert validation with an average score of 3.78 in the "very high/very feasible" category and users with an overall average score of 3.48 with category “very high/very feasible” for use.